2011
DOI: 10.1111/j.1467-8624.2011.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Third-Party Social Interaction and Word Learning From Video

Abstract: In previous studies, very young children have learned words while “overhearing” a conversation, yet they have had trouble learning words from a person on video. In Study 1, 64 toddlers (mean age = 29.8 months) viewed an object-labeling demonstration in one of four conditions. In two, the speaker (present or on video) directly addressed the child and in two, the speaker addressed another adult who was present or was with her on video. Study 2 involved two follow-up conditions with 32 toddlers (mean age = 30.4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 52 publications
(73 reference statements)
6
67
1
4
Order By: Relevance
“…Consistent with that argument, research with older toddlers and preschoolers has demonstrated that the lack of contingency reduces levels of interactivity and comprehension of video material (Calvert, Strong, & Gallagher, 2005;Crawley, Anderson, Wilder, Williams, & Santomero, 1999;Flynn & Whiten, 2008;Nielsen et al, 2008;Troseth, 2003;Troseth et al, 2006). There is limited evidence that similar social cues or expectations about interpersonal interactions help young infants and toddlers learn language from televised media (Linebarger & Vaala, 2009;O'Doherty, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Consistent with that argument, research with older toddlers and preschoolers has demonstrated that the lack of contingency reduces levels of interactivity and comprehension of video material (Calvert, Strong, & Gallagher, 2005;Crawley, Anderson, Wilder, Williams, & Santomero, 1999;Flynn & Whiten, 2008;Nielsen et al, 2008;Troseth, 2003;Troseth et al, 2006). There is limited evidence that similar social cues or expectations about interpersonal interactions help young infants and toddlers learn language from televised media (Linebarger & Vaala, 2009;O'Doherty, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Hence, any learning that took place must be viewed in this third-party context. It is also notable that utterances of this nature are commonly used in studies of third-party learning (e.g., Akhtar, 2005;Akhtar, Jipson, & Callanan, 2001;Herold & Akhtar, 2008;O'Doherty et al, 2011). Whether or not rates of imitation would drop if the demonstrating experimenter said nothing is a matter for future research.…”
Section: Resultsmentioning
confidence: 95%
“…This pattern of results highlights the pervasive nature of overimitation and young children's remarkable capacity for social learning. It also establishes, for the first time, that overimitation occurs robustly in third-party contexts in the absence of direct interaction, thereby adding to a growing body of literature documenting young children's ability to acquire novel object labels and actions via third-party processes (Akhtar, 2005;Akhtar et al, 2001;Floor & Akhtar, 2006;Herold & Akhtar, 2008;O'Doherty et al, 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Also, observing two people sharing attention engages our own attention more so than when people are not in any apparent interaction (Boeckler, Knoblich & Sebanz, 2011). This enhanced level of attention in turn can facilitate learning, for example, of new words (Akhtar, 2005;O'Doherty et al, 2011) or of new actions (Herold & Akhtar, 2008;Nielsen, Moore & Mohhammedaly, 2012).…”
Section: Shared Intentionsmentioning
confidence: 93%